Secretory Capacity of the Parathyroid Glands after Total Thyroidectomy in Normocalcemic Subjects - Anastasiou, Olympia E.; Yavropoulou, Maria P.; Papavramidis, Theodosis S.; Tzouvara, Chrysoula; Triantafyllopoulou, Konstantina; Papavramidis, Spiros; Yovos, John G. (The journal of clinical endocrinology and metabolism, 2012)
Context:Hypocalcemia, transient or permanent, represents a common complication after total thyroidectomy, but data on the secretory capacity of the parathyroid glands in thyroidectomized patients without clinical or biochemical hypocalcemia are limited.Study Design:To address this issue, we studied the parathyroid response to acute hypocalcemia induced by iv infusion of sodium bicarbonate in normocalcemic patients submitted to total thyroidectomy at the early postoperative period and 3 months later.Patients and Methods:Sixty patients who underwent total thyroidectomy for benign thyroid disease and did not develop clinical or biochemical hypocalcemia and hypoparathyroidism postoperatively and 50 healthy volunteers were included in the study. Patients (at 48 h and 3 months after surgery) and controls (after overnight fast) were subjected to a sodium bicarbonate infusion test.Results:In healthy volunteers plasma intact PTH increased significantly at 3 min after infusion (4.42 ± 0.15 ng/ml vs. 11.22 ± 0.5 ng/ml, P < 0.001) and gradually returned to baseline values. In the thyroidectomized patients, mean PTH levels were also increased after sodium bicarbonate infusion but to a significantly lesser degree compared with healthy controls (1.77 mean fold increase vs. 2.57 mean fold increase, respectively, P < 0.001). Using as criterion the lowest fold increase of plasma PTH levels at 3 min after infusion observed in healthy volunteers, 38% of the thyroidectomized patients at 48 h after surgery and 6.6% of the patients at 3 months after surgery demonstrated a diminished PTH response to acute hypocalcemia induced by sodium bicarbonate infusion.Conclusion:In thyroidectomized patients, normal postoperative calcium and PTH values do not exclude a reduced secretory response of the parathyroids to hypocalcemic stimuli.